Reality of Students’ Perceptions of Shari’a Faculty at Yarmouk University for the Causes of Weak Representation of the Values of Dress and Adornment - Al-yabroudi, Insherah Ahmed Tawfiq; Al-Rifa’e, Samira (Dirasat: Shari’a and Law Sciences, 2020)
This study aims at exploring the reality of the perception of the students of the Sharia Faculty at Yarmouk University for the causes of weak representation of the values of dress and adornment. In order to achieve this objective, the researchers follow a descriptive approach using a survey and a questionnaire that consisted of (43) items covering different areas: cognitive and intellectual, psychological and social and economic. The study finds that perception among the sample for causes of weak representation of the values of dress and adornment has been (high) on the total score of the scale and its sub-areas. Psychological reasons have ranked first followed by social and economic. However, reasons of cognitive and intellectual have come in the last rank. The results show that there are statistically significant differences at the level of significance (α = 0.05) in favor of aljilbab or alabayyah while no other differences are significant for the rest of the variables. In light of the study findings, the researchers recommend to sensitize the family and to confirm their role in controlling the values ​​of dress and adornment.